The role of the University lecturer at the Algerian University in enhancing the students’ linguistic security: The Faculty of Humanities and Social Sciences at the University of Jijel as a model - Menighed, Ahmed; Bouguerra, Belkacem (Journal of Human Sciences, 2022)
This study aimed to know the current reality of the linguistic security of the Algerian university student, and the role of at the Algerian University lecturer in its enhancing. This study adopted the descriptive methodology. The sample of this study )375( students in the faculty of human and social sciences in the University of Jijel. A questionnaire has been distributed among the students after checking its psychometric properties. Statistical processing used the statistical analysis software (SPSS), where arithmetic averages and standard deviations were calculated to know the level of the university lecturer role in enhancing the student’s linguistic security. The study found that the university lecturer in the faculty of human and social sciences in the University of Jijel has the language competencies that help him to enhance the linguistic security of the student to a big extent.